2011, Bike trial - characterisation of the event in view of the UCI worldchampionships from 2003 to 2011 - Tarnas, J.; Wielinski, D.; De La Fuente, B.; Arguelles, J. (Studies in Physical Culture and Tourism, 2011)
Bike trial is a relatively young cycling competition originating from motor sport. The study provides an analysis of bike trial on the basis of results from the UCI (Union Cycliste Internationale) world championships from 2003 to 2011. The starting point for the analysis was the data from 2003 related to sporting experience, forms of training and other issues. The competitors` age, numerical characteristics of national teams and their sports level were also analysed. The collected data were compared with data from the FIM motocycle trial world championships from 1997 to 2011. The age of bike trial finalists has been stabilised in recent years, which indicates the emergence of rules necessary for the training process. Similarly, the numbers of bike riders and national teams tend to remain constant. Nowadays top bike trial riders come from France, Germany, Spain and the United Kingdom, which to a large extent coincides with the popularity of motor trial in these countries. Bike trial is still an insufficiently described discipline and its further development requires a close study of the training process.